2004
DOI: 10.3928/0098-9134-20040601-05
|View full text |Cite
|
Sign up to set email alerts
|

The Transition of Elderly Patients Between Hospitals and Nursing Homes: Improving Nurse-to-Nurse Communication

Abstract: Lack of patient information is a particular problem when a patient is transferred from one health care facility to another. The lack of information needed to develop a timely and effective plan of care for an older adult transferred to the nursing home facility may exacerbate disruptions in the older adult's care. Also, adjustment or readjustment to the nursing home or hospital environment may be prolonged. Persistence of problems or difficulty in adjustment may then lead to exacerbation of the disease process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 4 publications
0
32
0
2
Order By: Relevance
“…46e48 Approximately 10% of patients arrive at SNFs without information and 30% arrive with inconsistent information under paper-based recordkeeping. 49 Under these circumstances, patients are highly vulnerable to adverse events, such as injuries, falls, infections acquired in health care settings, pressure ulcers, hip fractures, medical errors, and more. 50 Many of these issues may result in re-hospitalization, further raising the risk of care problems on future transfers.…”
Section: Discussionmentioning
confidence: 99%
“…46e48 Approximately 10% of patients arrive at SNFs without information and 30% arrive with inconsistent information under paper-based recordkeeping. 49 Under these circumstances, patients are highly vulnerable to adverse events, such as injuries, falls, infections acquired in health care settings, pressure ulcers, hip fractures, medical errors, and more. 50 Many of these issues may result in re-hospitalization, further raising the risk of care problems on future transfers.…”
Section: Discussionmentioning
confidence: 99%
“…Poor communication among physicians and nursing staff often negatively impact patient care quality, especially during patient care or transferring processes. The effects of poor communication may cause harm to patients [5], [6]. As a result, effective and good communication is the basis for providing quality patient care and ensuring patient safety.…”
mentioning
confidence: 99%
“…Multiple solutions to improve transitions in care have been proposed and selectively tested. Such solutions include care coordination (13 of 15 randomized trials showed no significant differences in subsequent hospitalizations and net savings) [15], the development of discharge checklists for hospitalists based on expert opinion [16], improved nurse to nurse communication using patient transition information checklists [17], and a movement towards information transfer interoperability [18][19][20]. There remains however, a lack of standardization of the necessary information data elements and processes as effective strategies to improve patient outcomes.…”
Section: Introductionmentioning
confidence: 99%